Protein digestibility and ammonia excretion in catfish Clarias gariepinus culture - Gunadi, Bambang; Harris, Enang; Supriyono, Eddy; Sukenda, .; Budiardi, Tatag (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT A series of experiments was performed to analyze protein digestibility, ammonia excretion, and also heterothropic bacteria and phytoplankton dynamics in the catfish Clarias gariepinus culture. In the digestibility experiment, catfish with an individual initial size of 43.67±0.83 g were stocked into 120 L conical fiberglass tanks at a density of 20 fish per tank. Fish were fed on with commercial diet supplemented with Cr2O3 indicator at a concentration of 1%. In the ammonia excretion experiment, catfish with an individual size of 111.6±9.5 and 40.6±3.4 g, respectively,  were placed into a 10 L chamber filled with 8 L of water. Total ammonia nitrogen (TAN) in the chambers were monitored every hour for six consecutive hours. In the bacteria and phytoplankton dynamics experiment, catfish were stocked in the 25 m2 concrete tanks which was divided into two compartments (catfish 10 m2, and heterotrof compartments 15 m2). Catfish with individual size of 42,5±0 g were stocked into the tanks at a density of 100 fish per tank. Water was recirculated from catfish compartments to heterotrophic compartments. Fish were fed with floating feed. Molasses as carbon source for heterotrophic bacteria was applied daily. The experiment was conducted for six weeks. The results showed that the protein digestibility was 61.97±7.24%. Larger fish (size of 111.6 g) excreted ammonia at a rate of 0.008±0.003 mg TAN/g fish-weight/hour, which was lower than that of the smaller catfish (size of 40.6 g), i.e. 0.012±0.004 mg TAN/g fish-weight/hour. Keywords: protein digestibility, ammonia excretion, catfish  ABSTRAK Serangkaian penelitian telah dilakukan untuk menganalisis ketercernaan pakan dan protein, ekskresi amonia, serta dinamika bakteri dan fitoplankton pada budidaya ikan lele (Clarias gariepinus). Pada penelitian ketercernaan pakan, ikan lele berukuran 43,67±0,83 g/ekor dipelihara dalam bak fiberglas berbentuk corong berukuran 120 L dengan kepadatan 20 ekor/bak. Ikan diberi pakan berupa pelet yang diberi indikator Cr2O3 sebanyak 1%. Pada penelitian ekskresi amonia, ikan lele berukuran 111,6±9,5 dan 40,6±3,4 g/ekor yang telah diberi makan sampai kenyang dimasukkan ke dalam stoples berisi 8 L air. Kadar amonia total (total ammonia nitrogen, TAN) di dalam stoples diukur setiap jam selama enam jam. Pada penelitian dinamika bakteri dan fitoplankton, ikan lele dipelihara pada bak beton berukuran 25 m2 yang disekat menjadi dua bagian yaitu bagian ikan lele (10 m2) dan bagian heterotrof (15 m2). Ikan lele dengan bobot awal 42,5 g/ekor ditebar ke dalam bak dengan kepadatan 100 ekor/bak. Air mengalir secara resirkulasi dari bagian ikan lele ke bagian heterotrofik dengan bantuan pompa. Pakan yang diberikan berupa pelet apung komersial. Molase ditambahkan setiap hari sebagai sumber karbon untuk pertumbuhan bakteri heterotrofik. Penelitian dilaksanakan selama enam minggu. Hasil pengamatan menunjukkan bahwa ketercernaan protein dari pakan yang diuji adalah 61,97±7,24%. Ikan lele berukuran besar (111,6 g/ekor) menghasilkan amonia sebanyak 0,008±0,003 mg TAN/g ikan/jam, lebih rendah dibandingkan dengan ikan yang berukuran lebih kecil (40,6 g/ekor), yaitu 0,012±0,004 mg TAN/g ikan/jam.  Kata kunci: ketercernaan protein, ekskresi amonia, ikan lele